An actin shell delays oocyte chromosome capture by microtubules - Verlhac, Marie-Hélène (J Cell Biol, 2018)
The large nuclei and tiny spindles of oocytes create a challenge for chromosome capture at M-phase entry. A contractile F-actin mesh in starfish oocytes delivers chromosomes to the spindle and Burdyniuk et al. (2018. J. Cell Biol. https://doi.org/10.1083/jcb.201802080) show that F-actin delays the capture of chromosomes until they are within reach of microtubules.